Borrelia burgdorferi BmpA-BBK32 and BmpA-BBA64: New Recombinant Chimeric Proteins with Potential Diagnostic Value - Weronika Grąźlewska; Bartłomiej Ferra; Monika Rudzińska; Lucyna Holec-Gąsior (Pathogens, 2021)
Currently, the diagnosis of Lyme disease is based mostly on two-tiered serologic testing. In the new generation of immunoenzymatic assays, antigens comprise whole-cell lysates of members of the Borrelia burgdorferi sensu lato (s.l.) species complex, with the addition of selected recombinant proteins. Due to the high diversity of members of the B. burgdorferi s.l. genospecies and the low degree of conservation among the amino acid sequences of their proteins, serodiagnostic methods currently in use are not sufficient for the correct diagnosis of borreliosis. Two divalent chimeric proteins (BmpA-BBK32 and BmpA-BBA64) were expressed in Escherichia coli. Following purification by one-step metal-affinity chromatography, preparations were obtained containing milligram levels of chimeric protein exhibiting electrophoretic purity in excess of 98%. Reactivity of the new chimeric proteins with specific human IgG antibodies was preliminarily determined by Western blot. For this purpose, 20 negative sera and 20 positive sera was used. The new chimeric proteins were highly reactive with IgG antibodies contained in the serum of patients suffering from borreliosis. Moreover, no immunoreactivity of chimeric proteins was observed with antibodies in the sera of healthy people. These promising results suggest that new chimeric proteins have the potential to discriminate between positive and negative sera.